2022
DOI: 10.1093/ajhp/zxac079
|View full text |Cite
|
Sign up to set email alerts
|

Four-factor prothrombin complex concentrate plus andexanet alfa for reversal of factor Xa inhibitor–associated bleeding: Case series

Abstract: Disclaimer In an effort to expedite the publication of articles related to the COVID-19 pandemic, AJHP is posting these manuscripts online as soon as possible after acceptance. Accepted manuscripts have been peer-reviewed and copyedited, but are posted online before technical formatting and author proofing. These manuscripts are not the final version of record and will be replaced with the final article (formatted per AJHP style and proofed by the authors) at a later time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…12,16 Liu et al reported a thrombosis incidence similar to this analysis (40%) and also combined previous data to find an incidence of in-hospital thromboembolism of 35% based on eight of 23 cases. 28 This study's data combined with that of Liu et al and Bradshaw et al shows a thromboembolism incidence of 15 cases in 37 total cases, or 40.54%. Unfortunately, the data in other case reports were not easily distinguished by neurologic bleed compared to bleeds of other locations, so this incidence of thromboembolism is an approximation and rates in only ICH patients cannot be fully estimated without further study.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…12,16 Liu et al reported a thrombosis incidence similar to this analysis (40%) and also combined previous data to find an incidence of in-hospital thromboembolism of 35% based on eight of 23 cases. 28 This study's data combined with that of Liu et al and Bradshaw et al shows a thromboembolism incidence of 15 cases in 37 total cases, or 40.54%. Unfortunately, the data in other case reports were not easily distinguished by neurologic bleed compared to bleeds of other locations, so this incidence of thromboembolism is an approximation and rates in only ICH patients cannot be fully estimated without further study.…”
Section: Resultssupporting
confidence: 55%
“…In fact, the most recent of such case series by Liu et al pooled thromboembolism incidence from previous studies and found that the combination of 4F-PCC and andexanet alfa led to an incidence of thromboembolism of 35%. 28 Another recent case series by Bradshaw et al found that 2 of 5 patients (40%) experienced thromboembolism. 29 This analysis examines patients who received both 4F-PCC and andexanet alfa for reversal of factor Xa inhibitor-associated nontraumatic intracranial bleeding at a large academic medical center, with the goal of defining safety and efficacy outcomes.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Within 3 days, two of the five patients developed an ischemic or thromboembolic complication and two intrahospital deaths occurred. Liu et al [89] reported a 40% thromboembolism rate and an in-hospital mortality of 60% in five patients who received 4F-PCC and andexanet concomitantly. They further investigated the available literature identifying 23 cases of concomitant therapy of which 8 patients developed thromboembolic complications (35%).…”
Section: Discussionmentioning
confidence: 99%
“…Given the lack of clinical data on the safety of the combined use of AA and prothrombin complex concentrate (PCC), activated prothrombin complex concentrate (aPCC), recombinant factor VIIa, fresh frozen plasma (FFP) or whole blood, such use should be avoided unless absolutely necessary. Several case series have been published on this topic, with the results highlighting the potentially increased thrombotic risk associated with the use of the AA and PCC combination [18,19].…”
Section: Interactionsmentioning
confidence: 99%